2016
DOI: 10.1590/s1678-9946201658071
|View full text |Cite
|
Sign up to set email alerts
|

Status of the American Tegumentary Leishmaniasis in the State of Rio De Janeiro , Brazil, From 2004 to 2013

Abstract: SUMMARY The aim of the present study was to analyze the status of the American Tegumentary Leishmaniasis (ATL) in the state of Rio de Janeiro, from 2004 to 2013, through its spatiotemporal distribution. We also described variables considered relevant to the epidemiology of the disease, such as the clinical form, gender, ethnic group, age group, and progression of disease. This is a descriptive study, which used notified secondary data from the Brazilian Information System of Notifiable Diseases (SINAN), Minist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…The severity and outcome of disease seems also to be sex-dependent, with male sex being suggested as a risk factor for death or relapse after treatment-once again especially after the age of puberty [1,25,[28][29][30][31][32][33]. Unfortunately, no information on outcome of the disease was available for our study.…”
Section: Discussionmentioning
confidence: 99%
“…The severity and outcome of disease seems also to be sex-dependent, with male sex being suggested as a risk factor for death or relapse after treatment-once again especially after the age of puberty [1,25,[28][29][30][31][32][33]. Unfortunately, no information on outcome of the disease was available for our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a descriptive study conducted by Vita et al ., supported by data from the Brazilian Information System of Notifiable Diseases (SINAN) and the Brazilian Institute of Geography and Statistics (IBGE), 1,470 cases of CL were analyzed; 87.89% were of the cutaneous clinical form, and there were higher incidences in the white ethnic group (49.72%) and in the 20- to 39-year-old age group (32.44%) 27 . These researchers concluded that there was a decrease in the number of cases based on a coefficient of detection from 1.44 per 100,000 inhabitants in 2004 to 0.20 per 100,000 in 2013.…”
Section: Epidemiologymentioning
confidence: 99%
“…A preferência pelo uso de Antimonial Pentavalente, assim como preconizado pelo MS, em ambas as doenças como droga inicial utilizada levanta questionamentos em relação à segurança do tratamento oferecido em um primeiro momento e como está sendo conduzido posteriormente devido ao efeito cardiotóxico deste medicamento², o qual já foi utilizado como justificativa para mortes em indivíduos com mais de 70 de anos 12 . Portanto, devem-se ponderar novamente os riscos propostos aos pacientes já debilitados, haja vista que a Anfotericina B lipossomal é contrária e recomendada em casos de hipersensibilidade dos outros tratamentos 13 .…”
Section: Discussionunclassified